PERANCANGAN APLIKASI PEMESANAN CATERING BERBASIS MOBILE ANDROID - Mamay Syani; Nindi Werstantia (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Ordering catering is an activity undertaken by customers to buy products in the form of food packages. In Cimahi Catering catering ordering process is done by customers by coming directly to the location or calling to Cimahi Catering. Based on interviews with the authors related parties, in the process of ordering catering there are some customers who complain about the order process is due to take time, energy and more costs. In the case of recording data ordering was deemed less effective because the data is still conventional. This is at risk of logging errors. As a solution of these problems the authors build an Application Ordering Catering Based Android Mobile to assist in the process of ordering catering by customers and the management of reservation data catering by the Cimahi Catering. Research methodology used is Extreme Programming method. In making this application the author uses android programming base and MySQL as the data storage. This application is made to efficiently time, effort and produce accurate information. The results of testing the built application has a performance that suits the needs of the user. Based on the results of User Acceptance Test get a positive response with 85% percentage. Keyword: Android, application, catering, mobile, ordering, uat